Genetic Diversity and Phylogenetic Relationships of Castor fiber birulai in Xinjiang, China, Revealed by Mitochondrial Cytb and D-loop Sequence Analyses - Linyin Zhu; Yingjie Ma; Chengbin He; Chuang Huang; Xiaobo Gao; Peng Ding; Linqiang Zhong (Animals, 2025)
Castor fiber birulai is a subspecies of the Eurasian beaver that has a relatively small population size compared to other Castor subspecies. There is limited genetic research on this subspecies. In this study, mitochondrial cytochrome b (Cytb) and D-loop sequences were analysed in genetic samples obtained from 19 individuals residing in the Buergen River Basin, Xinjiang, China. The Cytb region presented a single haplotype, whereas three haplotypes were identified in the D-loop region. The genetic diversity within the Chinese population was low (D-loop Hd = 0.444; Pi = 0.0043), markedly lower than that observed in other geographical populations of C. fiber. Phylogenetic reconstructions and haplotype network analyses revealed substantial genetic differentiation between C. f. birulai and other Eurasian lineages (Fst > 0.95), supporting the status of C. f. birulai as a distinct evolutionary lineage. Although the genetic distance between the Chinese and Mongolian populations was relatively small (distance = 0.00269), significant genetic differentiation was detected (Fst = 0.67055), indicating that anthropogenic disturbances—such as hydraulic infrastructure and fencing along the cross-border Bulgan River—may have impeded gene flow and dispersal. Demographic analyses provided no evidence of recent population expansion (Fu’s Fs = 0.19152), suggesting a demographically stable population. In subsequent studies, we recommend increasing nuclear gene data to verify whether the C. f. birulai population meets the criteria for Evolutionarily Significant Unit classification, and strengthening cross-border protection and cooperation between China and Mongolia.